SINERGISITAS PEMERINTAHAN DAERAH DAN LEMBAGA ADAT DALAM MELAKSANAKAN PELESTARIAN KEBUDAYAAN KENDURI SKO DI KERAPATAN ADAT NEGERI JUJUN - M Dhany Al Sunah,; Antri Mariza Qadarsih,; Tomi Maswira, (Jurnal Cakrawala Ilmiah, 2022)
Indonesia is a country rich in cultural diversity spread throughout its territory, one of which is the Kenduri Sko Culture of the Kerinci Nation in Kerapatan Adat Jujun Country, in its management that is authorized is the local government and customary institutions followed by the role of the community, which forms a collaboration in carrying out conservation, namely synergy.The research objective is to describe and analyze the implementation of synergy, supporting factors and inhibitors of synergy, as well as the results of synergy in carrying out conservation. This study uses a qualitative descriptive research method.The synergy of the local government and customary institutions in carrying out the preservation of the culture of kenduri sko in the density of the jujun customs turned out to be unsuccessful, seen from the implementing actors, programs, and facilities and infrastructure. The synergy was not carried out so well that it had not brought positive results to the preservation of the culture of kenduri sko in the density of jujun customs.The supporting factors are the contents of regulations that are easy to understand, and the attitude of the government that has the desire to be able to be involved in the implementation of the preservation of the culture of kendo sko. The inhibiting factor is coordination that does not work well, and there is no specific regulation that regulates the issue of preserving the Kerinci Nation's Kenduri Sko Culture